2021
DOI: 10.5005/jp-journals-10006-1857
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Lockdown on Admissions to a Tertiary Maternity Hospital in Srinagar

Abstract: Introduction:The first case of new pneumonia of unknown origin was found in Wuhan (China) on December 31, 2019. The causative virus was identified from throat swab samples in the Chinese Centre for Disease Control and Prevention (CCDC) on January 7, 2020, and it was named severe acute respiratory syndrome coronavirus (SARS-CoV-2). Subsequently, World Health Organization (WHO) renamed it COVID-19. COVID-19 was a highly infectious newly discovered coronavirus, which led to a worldwide pandemic. It has shown an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Overall, 14 studies reported data from four low-income countries ( 34–47 ), 21 studies were focused on 13 lower-middle income countries ( 48–68 ), seven studies were conducted in five upper-middle income countries ( 69–75 ) and three were multi-centred ( 76–78 ). Out of 45 included studies, 11 studies were cross-sectional ( 41 , 45 , 48 , 51 , 55–57 , 65 , 69 , 70 , 76 ), 14 were pre-post studies ( 34 , 38 , 49 , 50 , 52 , 53 , 56 , 62 , 64 , 72–75 , 77 ), nine were time-series ( 35 , 37 , 39 , 43 , 58 , 59 , 67 , 71 , 78 ), five were mixed methods ( 36 , 42 , 47 , 61 , 63 ) and six were qualitative ( 40 , 44 , 46 , 54 , 60 , 68 ). The included studies’ characteristics are summarised in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 14 studies reported data from four low-income countries ( 34–47 ), 21 studies were focused on 13 lower-middle income countries ( 48–68 ), seven studies were conducted in five upper-middle income countries ( 69–75 ) and three were multi-centred ( 76–78 ). Out of 45 included studies, 11 studies were cross-sectional ( 41 , 45 , 48 , 51 , 55–57 , 65 , 69 , 70 , 76 ), 14 were pre-post studies ( 34 , 38 , 49 , 50 , 52 , 53 , 56 , 62 , 64 , 72–75 , 77 ), nine were time-series ( 35 , 37 , 39 , 43 , 58 , 59 , 67 , 71 , 78 ), five were mixed methods ( 36 , 42 , 47 , 61 , 63 ) and six were qualitative ( 40 , 44 , 46 , 54 , 60 , 68 ). The included studies’ characteristics are summarised in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 14 studies reported data from four low-income countries (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47), 21 studies were focused on 13 lower-middle income countries , seven studies were conducted in five upper-middle income countries (69)(70)(71)(72)(73)(74)(75) and three were multi-centred (76)(77)(78). Out of 45 included studies, 11 studies were cross-sectional (41, 45, 48, 51, 55-57, 65, 69, 70, 76), 14 were pre-post studies (34,38,49,50,52,53,56,62,64,(72)(73)(74)(75)77), nine were time-series (35,37,39,43,58,59,67,71,78), five were mixed methods (36,42,…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…A total of 82% of the PHC team was extremely satisfied with the mentoring provided, 16% were satisfied, and only 2% were neutral as shown in Figure 4. [9][10][11]…”
Section: Increase In Proportion Of Elective Surgeriesmentioning
confidence: 99%
“…The COVID-19 pandemic proved to be a blessing in disguise in unifying the segregated units of public healthcare via technology and smartphones. 9,10 National Health Mission selected Tamil Nadu's "mentoring" concept as best practice and was published in The Hindu on 24 January 2021. 11 "Mentoring" has definitely helped in bridging the disconnect that existed between the field and institutional care for high-risk pregnant women.…”
Section: Orcidmentioning
confidence: 99%